Subchondral bone microarchitecture and mineral density in human osteoarthritis and osteoporosis: A regional and compartmental analysis. Issue 12 (19th March 2021) - Li, Yunfei; Liem, Yulia; Dall'Ara, Enrico; Sullivan, Niall; Ahmed, Haroon; Blom, Ashley; Sharif, Mohammed
Abstract: Osteoarthritis (OA) and osteoporosis (OP) are historically considered to be inversely correlated but there may be an overlap between the pathophysiology of the two diseases. This study aimed to investigate the subchondral bone microarchitecture and matrix mineralization, and the association between them in OA and OP in relation to the degree of cartilage degeneration. Fifty‐six osteochondral plugs were collected from 16 OA femoral heads. They were graded on a regional basis according to the stages of cartilage degeneration, as evaluated by a new macroscopic and a modified microscopic grading system. Twenty‐one plugs were collected from seven femoral heads with OP. Plugs were scanned by microcomputed tomography and the microarchitectural and mineral properties were obtained for both subchondral plate and trabecular bone. Microarchitecture and material and apparent densities of subchondral bone in OP were similar to regions with early cartilage degeneration but different from regions with advanced cartilage degradation in OA femoral heads. Subchondral trabecular bone was more mineralized than subchondral plate in both OP and OA, and this compartmental difference varied by severity of cartilage degradation. Furthermore, the relationship among trabecular bone volume fraction, tissue mineral density, and apparent bone density was similar in OP and different stages of OA. Subchondral bone microarchitecture and mineral properties in OP are different from OA in a regionalized manner in relation to stages of cartilage degeneration. Both regional and compartmental differences at structural, material, and cellular levels need to be studied to understand the transition of OA subchondral bone from being osteoporotic to sclerotic.